Pembinaan Kreatifitas Siswa melalui Kegiatan Ekstra Kurikuler Kelompok Ilmiah Remaja (KIR) di MAN 2 Kuantan Singingi - Tiffani; Martin Kustati; Rezki Amelia; Mardianto; Nurhasnah (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This coaching aims to increase students' creativity in writing scientific papers and achieve success in participating in scientific writing competitions. Apart from achieving achievements in writing scientific papers, coaching also aims to form students' attitudes of obedience, perseverance and discipline in writing scientific papers. KIR Extracurricular is a forum for students who have an interest in writing scientific papers at MAN 2 Kuantan Singingi. The method used in this mentoring is the service learning method by following three stages, namely: the preparation stage, namely the preparation of KIR Extracurricular learning modules, the service stage, fostering students' creativity in writing, which is held in one meeting on Saturdays, and the reflection stage, namely looking at the results of written work. students who have been created. The target for coaching is students who are members of the KIR Extracurricular consisting of classes X-XII. The results of this assistance show that fostering student creativity through KIR extracurricular activities, it was found that there were changes and increases in student creativity in writing scientific papers at MAN 2 Kuantan Singingi. This coaching runs smoothly by following all stages with the hope of improving student achievement in writing scientific papers.